Mixing Colors, Making Designs: A. S. Byatt's "Racine and the Tablecloth, " "Rose-Coloured Teacups, " and "Sugar". Issue 3 (27th May 2017) - Stewart, Jack
ABSTRACT: Themes of intellectual design, decorative pattern, color stimulus, visual art, and creativity form the framework of A. S. Byatt's Sugar and Other Stories . In "Racine and the Tablecloth, " "Rose-Coloured Teacups, " and "Sugar, " Byatt translates emotion, intellect, sense, and memory into a language of "fictionalized autobiography" that self-reflexively sheds light on her creative development. The dramatic language of Racine provides a model of intellectual design that contrasts with the embroidered pattern of a tablecloth. A retrospective vision of rose-colored teacups on a tablecloth signifies Victorian décor, implicitly compared with a still life by Matisse (cover illustration). The mixed colors of molten sugar awaken a child's aesthetic sense in a way later associated with Van Gogh's paintings and ekphrastically reflected in the novel Still Life . The three stories examined reveal important aspects of Byatt's fictional art and aesthetic values.